Aquecimento em colunas de acreção de estrelas T Tauri - Alana Paixao de Sousa (2011)
Young low mass stars that show signs of accretion, the classical T Tauri stars (CTTSs), present a significant number of emission lines in their spectra. These emission lines, thought to be produced in accretion columns, are often modelled in order to obtain physical parametersof the star-disk system, such as the mass accretion rate. However, the temperature structure of accretion columns is still poorly understood. In this work, we present a study of the temperature profile of accretion columns found around CTTSs. We consider young stellar objects (~106 year) of low mass (M* ~ 2 M), which have accretion disks in keplerianrotation. We adopt a magnetospheric accretion model, where the central star has a dipole magnetic field that disrupts the disk at a distance from the star (rtr 0.1 AU) near the co-rotation point. The accreting gas follows stellar magnetic field lines from rtr to the central star. In order to determine the temperature profile in the accretion column, weuse the first law of thermodynamics, solved for the hydrogen atom in a steady state. This result gives us the heat equation, which was solved with the rate equation for the hydrogen atom, considering the processes of collisional excitation and de-excitation (with protons and electrons), radiative recombination, spontaneous transition, collisional ionization and photoionization. We use adiabatic compression as a heating mechanism, following Martin (1996), but we also analyze heating by X-rays, coming from the star. We consider as cooling mechanisms emission by Ca II and Mg II lines and bremsstrahlung. We then obtain thetemperature structure for acrretion funnels and the main physical processes which heat and cool the gas. We also found that the accretion rate of mass and the X-ray luminosity, are the most important parameters for the thermal structure of gas.